El Aguilucho Jote (Buteo albonotatus) en Argentina - Areta, Juan I.; Bodrati, Alejandro; Klavins, Juan; Almirón, Daniel; Hulsberg, Hugo; Mangini, Giselle (Nuestras Aves, 2014)
Este artículo no cuenta con un resumen.